Population biology and sexual dimorphism in the freshwater prawn Atya scabra (Decapoda: Atyidae) in the De Contas River, Bahia, Brazil - de Barros, Matheus Souza Ferreira (2020)
Abstract. Introduction: Crustaceans have economic and ecological importance and the role of caridean crustaceans in lentic environments is crucial to maintain the trophic structure. The species Atya scabra is occasionally associated with fisheries, especially in Northeast and Northern Brazil. Objective: To determine the population structure, reproductive period, patterns of growth and distribution of size classes among sexes in a population of the prawn A. scabra in the De Contas River, Bahia, Brazil. Methods: Individuals were sampled in a period of one year by passing sieves through marginal vegetation and using dragnets. In the laboratory, we recorded the sex of the individuals and measured them using a pachymeter with 0.001 mm precision. The dimensions measured were CL (carapace length), TL (total length) and CW (carapace width). In order to analyze data, linear models for the relationships CL × CW were constructed and the type of allometry for each sex was determined. Individuals were grouped into size classes of 5 mm intervals. A chi-square test (χ2) was used to test deviation from the 1:1 sex ratio. The proportion of ovigerous females was registered for each month to determine the breeding period. Results: A total of 517 individuals were collected, 328 were males and 186 females of which 169 were ovigerous. Males showed a polymodal distribution in size classes and were significantly larger than females, which presented a unimodal distribution in size classes. The observed growth patterns demonstrated that both sexes present negative allometry. However, sexual dimorphism was detected when comparing the growth parameters. Ovigerous females were sampled the entire year and size-frequency data demonstrated that recruitment also occurs throughout the year, which allowed us to classify their reproduction as continuous. Conclusions: Our data is essential to draw sustainable fishery management strategies. We suggest a minimum capture size of 70 mm and capture restrictions from May to August. Key words: ecology; freshwater; limnology; conservation; morphometry.